Ethnobotanical, phytochemical, and pharmacological properties of nepenthes species: a review - Sanusi, Shuaibu Babaji; Abu Bakar, Mohd Fadzelly; Mohamed, Maryati; Sabran, Siti Fatimah; Mainasara, Muhammad Murtala (Innovare Academic Sciences Pvt Ltd., 2017)
The genus Nepenthes (Nepenthaceae) has been utilized in folk medicine for a long time in India and Southeast Asia countries. They are used in the treatment of leprosy, cholera, night blindness, gastrointestinal discomfort, dysentery, stomachache, and bed-wetting among others. This review highlights the ethnobotanical uses, phytochemicals, and pharmacological activities of both crude extracts and pure bioactive compounds of Nepenthes spp. The phytochemical compounds isolated from Nepenthes species include flavonoids, terpenoids, tannins, alkaloids, and steroids among other phytochemicals. A wide range of pharmacological activities was exhibited by the crude extracts and pure bioactive components such as antibacterial, antifungal, antimalarial antioxidant, antidiabetic, antiosteoporotic, anti-inflammatory, cytotoxicity, and hypolipidemic activities. This review revealed that many active compounds are present in Nepenthes spp. However, many pharmacological screenings such as anticancer, antiviral, wound healing, antihelminthic, antidiarrheal properties, among others have not been carried out yet. Therefore, more biological investigations and phytochemical screenings are required to fully explore the genus Nepenthes which may lead to development of new therapeutic agents.